E-Readiness of Government Staff toward E-Government Programs In Denpasar Municipality - Padangratha, Ida Ayu Cininta (JPAS (Journal of Public Administration Studies), 2016)
This research is intended to analyse the readiness of non-IT staff toward e-government programs. It is located in Denpasar Municipality. The method employed in this study is quantitative in nature with questionnaires distribution. There were 111 respondents who participated in this research. The data analysis methodÂ  used is Unified Technology Acceptance of Use Technology Model (UTAUT), which is calculated by Partial Least Square and Force Field Analysis. The result is from 15 hypotheses, only 4 are accepted. From Partial Least Square calculation, facilitating condition and social influence are determined as the most dominant and significant variables. Furthermore, through force field analysis, facilitating condition is determined as the driving force, and social influence as the restraining force. TNB total score for the driving force is 8.51, while restraining force TNB total score is 5.37. Thus, the driving force for TNB total score is 3.15 point higher than the restraining force. On the scale 0-5, non-IT staffâ€˜s readiness toward e-government programs is considered moderate. However, if we see each TNB score, we can see that each variable has low score. Hence, it is appropriate to formulate strategy focusing on facilitating condition and social influence.